Sand pipes as potential indicators of seismicity in the Casa Grande Formation, northwestern Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2024)
In fluvial deposits of the Casa Grande Formation (Middle Eocene), a suite of Soft Sediment Deformation Structures (SSDS) have been identified, the genesis of which could be associated with seismic movements (seismites). This formation has been linked to the early stages of evolution of the Andean foreland basin in the transition between the Puna and the Eastern Cordillera. This study focuses on describing and interpreting discordant structures understood as sand pipes and the processes related to their formation. These structures are characterized by an inverted funnel morphology and are distinguished by their metric-scale dimensions. Associated with the sand pipes, disturbed lamination, pillar and plate structures, clastic dikes, and load casts were recognized and described. Considering the characteristics of these structures, liquefaction and fluidization processes are interpreted as the formative mechanisms. Based on the deposit and structures characteristics, presence in restricted stratigraphic intervals, lateral continuity, vertical repetition, proximity to faults, and similarity to structures produced by recent earthquakes, seismic events are proposed as the triggering mechanism for the deformation.
Keywords: soft sediment deformation structures; Paleogene; seismites; water escape; Eastern Cordillera